The Influence of Transformational Leadership, Academic Supervision, and Interpersonal Communication on the Performance of XYZ Elementary School Teachers at Bekasi - Junita Junita; Innocentius Bernarto (Jurnal Indonesia Sosial Sains, 2025)
The success of a teacher's performance is inseparable from the active role of all components of the school environment that support educational success. Collaboration among school leaders, teachers, administrative staff, and parents is required. School leaders must also be proactive in assisting teachers with their problems. This study aimed to determine the positive influence of transformational leadership, academic supervision, and interpersonal communication on the performance of teachers at SD XYZ in Bekasi. The research was conducted at SD XYZ Bekasi starting in October 2024 with a sample of all teachers at SD XYZ Bekasi, totaling 47 teachers. The data obtained were analyzed using SmartPLS 3.0. This quantitative study employed a structural equation modeling (SEM) approach and IPMA. The results showed that transformational leadership had a positive impact on academic supervision, and interpersonal communication had a positive impact on academic supervision transformational leadership had a positive impact on teacher performance, academic supervision had a positive impact on teacher performance, interpersonal communication had a positive impact on teacher performance at SD XYZ Bekasi.